Analisis Laporan Akuntabilitas Kinerja Instansi Pemerintah Menggunakan Value for Money pada Dinas Perhubungan Kabupaten Bulukumba - Tenri Awaru, Andi; Sahade; Samsinar (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the performance accountability of the Bulukumba Regency Transportation Agency government agency based on Value for Money analysis that focuses on three main elements: economics, efficiency, and effectiveness. The research variable is the Government Agency Performance Accountability Report (LAKIP) as the dependent variable (Y) which is measured by the Value for Money concept as the independent variable (X). The Government Agency Performance Accountability Report data focuses on the Bulukumba Regency Transportation Agency for 2021-2023. The results show that the Bulukumba Regency Transportation Agency Government Agency Performance Accountability Report (LAKIP) for 2021-2023 has not fully met the Value for Money concept. This is because the performance only meets the efficiency and effectiveness aspects, while the economic aspect is still considered less economical. The budget realization rate which is always above 90% indicates that the budget allocation is not fully efficient, so the principle of saving in the use of inputs has not been optimally achieved.